2017
DOI: 10.4103/sajc.sajc_202_17
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib in Indian patients with T790M-positive advanced nonsmall cell lung cancer

Abstract: Conclusion Carcinoma breast in male management principles are translated from our understanding of breast cancer in women. The prognosis is dependent on stage of the disease and HR status. Most of the analysis in our study was in concordance with the available data except the stage at presentation. In our study, the predominant stage at presentation was Stage II. This may be due to raising awareness among the population in the metro cities, which is a welcome trend. Financial support and sponsorship Nil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…[6] The first Indian report of 13 patients showed good symptom control as well as an overall response rate of 55% (6/11 evaluable patients). [8] This was comparable to the objective response rate to osimertinib of 71% in AURA3. [6] This issue of IJMPO presents prospective observational data on 90 patients who had progressive disease while on EGFR TKI.…”
supporting
confidence: 52%
“…[6] The first Indian report of 13 patients showed good symptom control as well as an overall response rate of 55% (6/11 evaluable patients). [8] This was comparable to the objective response rate to osimertinib of 71% in AURA3. [6] This issue of IJMPO presents prospective observational data on 90 patients who had progressive disease while on EGFR TKI.…”
supporting
confidence: 52%
“…A recent retrospective European study in 135 patients reported that chemotherapy after progression on rst line TKI resulted in a median PFS of 5.4 months (95% CI, 4.7-6.1), and median OS of 15.3 months (95% CI, 116 − 18.9) [40]. In an earlier real world study report, we found that osimertinib at 80 mg a day in the second line and beyond setting for 17 patients with EGFR T790M mutation led to an ORR of 55% and DCR of 90.9%; survival data were immature at the time of this report [41]. In our present study, reduced frequency osimertinib was used in 82.4% patients with EGFR T790M mutations in the second line and beyond setting, and resulted in an ORR of 29.4%, DCR of 70.5%, median PFS of 5.9 months, and median OS of 17.6 months.…”
Section: Discussionmentioning
confidence: 56%
“…A recent retrospective European study in 135 patients reported that chemotherapy after progression on first-line TKI resulted in a median PFS of 5.4 months (95% CI, 4.7–6.1), and median OS of 15.3 months (95% CI, 116–18.9) [ 26 ]. In an earlier real world study report, we found that osimertinib at 80 mg a day in the second line and beyond setting for 17 patients with EGFR T790M mutation led to an ORR of 55% and DCR of 90.9%; survival data were immature at the time of this report [ 27 ]. In our present study, 82.4% of the patients who received reduced frequency osimertinib had EGFR T790M mutation in the second line and beyond setting; therapy resulted in an ORR of 29.4%, DCR of 70.5%, median PFS of 5.9 months and median OS of 17.6 months.…”
Section: Discussionmentioning
confidence: 92%